Toleransi Kekeringan Sawi Hijau pada Osmopriming Benih dan Interval Pemberian Air Sampai Kapasitas Lapang - Kesmayanti, Novisrayani (Universitas Pattimura, 2024)
Green mustard (Brassica chinensis L.) is widely cultivated commercially. The problem is that some farmers use self-propagated seeds with simple processing and storage facilities so that the quality of the seeds is not guaranteed and is low. Apart from seed quality, limited water, especially during cultivation in the dry season or on dry land, is also a limiting factor. Low seed quality can be overcome by invigorating seeds using the osmopriming method; water limitations can be overcome by periodically fulfilling field capacity water. This research aimed to measure and analyze the growth response and drought tolerance of green mustard plants in seed osmopriming treatments and setting water intervals to field capacity. The research was carried out at the Experimental Field and Plant Physiology Laboratory, Faculty of Agriculture, IBA University in Palembang, in October-December 2020. The research used a 5x3 Factorial Randomized Block Design, with 3 replications, so there were 45 experimental units. The first factor was seed osmopriming, O1= control (water), O2= CaCl2 1.5% - soaked 4.5 hours, O3=CaCl2 3%-soaked for 4.5 hours, O4=KNO3 1%-soaked for 5 hours, and O5=KNO3 1.5%-soaked for 5 hours. The second factor was watering interval to field capacity, P1= every 24 hours, P2= every 72 hours, and P3= every 120 hours. The research results showed that osmopriming produced values of germination power, vigor index, growth speed, growth simultaneity and maximum seed growth potential of 100%, and with fast and relatively the same germination age of 4.22 to 5.05 days after planting (dap). In plants 14 dap, osmopriming with 1.5% KNO3 and soaking for 5 hours produced plants with the highest height, number of leaves and root length. The interaction of osmopriming with intervals of water supply to field capacity every 24 hours and 72 hours produces plants with the highest height, number of leaves, root length and weight/yield. There was a decrease in plant growth and yield at the interval of providing water to field capacity every 120 hours. The drought tolerance of green mustard is in watering intervals to field capacity every 72 hours.